Women Group Empowerment in Utilizing Pineapple Skin Waste became Shampoo in Beluk, Pemalang, Central Java - Rina Yuniarti; Ayu Munti Nilamsari; Astrid Noviana; Muhammad Rizqi; Kisnun Baani; Diana Nur Afifah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Pineapple is one of the tropical fruits that grows a lot in Indonesia, Beluk Village, Belik District, Pemalang Regency is one of the large pineapple producers. At present there are various processed products from pineapple. However, there is a side product of pineapple skin waste from the processing of pineapple which has not been processed properly. Research on the content and benefits has been carried out in the laboratory, but the results have not been well socialized. Pineapple contains bromelin enzymes including the skin. The bromelin enzyme is a proteolytic enzyme that is antimicrobial, so it can be used as dandruff shampoo. Therefore, transfer of knowledge to reduce pineapple skin waste is very necessary.This study prioritizes participatory functions of women group (PKK). The main purpose of this study is transfer of knowledge to reduce pineapple skin waste by providing training to PKK group in utilizing pineapple skin waste as shampoo. Meanwhile, PKK group can earning extra income from shamppo produced from pineapple skin waste.The social engineering approach is used in this study, a combination of a social or community development approach with a simple method of processing pineapple skin waste. A social approach is needed to increase public awareness to utilize pineapple skin waste. The technical approach is used for laboratory-scale study on pineapple skin. Meanwhile, it also simplifies the processing of pineapple skin waste into shampoo so that it can be widely adopted by the community. Keywords: pineapple skin waste, community empowerment, shampoo of pineapple skin